2015
DOI: 10.1111/jch.12715
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa Flavanol Cardiovascular Effects Beyond Blood Pressure Reduction

Abstract: The protective cardiovascular (CV) effect of cocoa flavanol has been a target of many recent clinical prospective and retrospective investigations. Epidemiological data in different patient cohorts revealed an association between higher intake of flavanol-rich foods and decreased incidence of CV events, especially stroke and myocardial infarction. Cocoa flavanol has been shown to reduce systolic (2.8 mm Hg) and diastolic (2.2 mm Hg) office blood pressure (BP). Greater BP reduction has been found in hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…This performance may be due to the effects of flavonoids on blood pressure and peripheral and central blood flow [26, 27]. The beneficial effects of flavanols also include improved endothelial function, anti-inflammatory potency, inhibition of platelet activation, and increased vasodilatory capacity [28]. EPI is the most physiologically potent compound, and primarily accounts for the biological effects of flavanols [13].…”
Section: Discussionmentioning
confidence: 99%
“…This performance may be due to the effects of flavonoids on blood pressure and peripheral and central blood flow [26, 27]. The beneficial effects of flavanols also include improved endothelial function, anti-inflammatory potency, inhibition of platelet activation, and increased vasodilatory capacity [28]. EPI is the most physiologically potent compound, and primarily accounts for the biological effects of flavanols [13].…”
Section: Discussionmentioning
confidence: 99%
“…Cocoa flavanols are also able to inhibit platelet activation, adhesion, and aggregation, mechanisms that play a central role in the development of endothelial dysfunction and atherosclerosis ( 109 ). Indeed, activated platelets secrete a number of adhesion molecules, such as P-selectin and C40 ligand, release inflammatory mediators into the local microenvironment ( 110 ), stimulate the chemotaxis of leukocytes to the site of inflammation ( 111 ), and generate ROS, reducing NO bioavailability and contributing to endothelial dysfunction and thrombosis ( 112 ).…”
Section: Putative Mechanismsmentioning
confidence: 99%
“…Therefore, interest has been directed towards other bioactive compounds found in fruit and vegetables, namely, polyphenols (Duthie et al , ) that might mediate the benefits independent of the abundant antioxidants. Epidemiological studies have also shown that polyphenols found in berries (Ellingsen et al , ; Li et al , ), chocolate (Jumar and Schmieder, ; Larsson et al , ), coffee (Grosso et al , ) and red wine (Cosmi et al , ) are associated with slower CVD progression. However, given their low bioavailability, the assumption that the observed health beneficial effects are driven by their direct antioxidant activity (chemical antagonism) seems very unlikely.…”
Section: Antioxidant Therapies In Cvdmentioning
confidence: 99%